Representing the People 2014
DOI: 10.1093/acprof:oso/9780199684533.003.0005
|View full text |Cite
|
Sign up to set email alerts
|

Electoral Rules and Legislators’ Personal Vote-seeking

Abstract: The policy positions parties choose are central to both attracting voters and forming coalition governments. How then should parties choose positions to best represent voters? Laver and Sergenti show that in an agent-based model with boundedly rational actors a decision rule (Aggregator) that takes the mean policy position of its supporters is the best rule to achieve high congruence between voter preferences and party positions. But this result only pertains to representation by the legislature, not represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…personal vote seeking based on the PartiRep data we use does not find such an effect but instead shows that district magnitude decreases personal vote seeking throughout (André et al, 2014). Based on this finding we do not pursue the interactive argument advanced by Carey and Shugart.…”
Section: Hypothesesmentioning
confidence: 62%
See 3 more Smart Citations
“…personal vote seeking based on the PartiRep data we use does not find such an effect but instead shows that district magnitude decreases personal vote seeking throughout (André et al, 2014). Based on this finding we do not pursue the interactive argument advanced by Carey and Shugart.…”
Section: Hypothesesmentioning
confidence: 62%
“…Single member districts give all MPs incentives to present themselves as individuals to build a personal vote. Larger districts, by contrast, make it more likely that individual MPs are perceived solely as members of their parties and thus have few incentives to present themselves as individuals (Cain et al, 1987;Zittel and Gschwend, 2008;André et al, 2014). 6 We focus on the binary distinction between single member and multi member districts because it provides clear theoretical expectations whereas one may doubt whether differences on higher levels, say between districts of 17 and 18 members, still affect personal vote seeking.…”
Section: Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…To attract personal votes that increase their chances of re-election, representatives in legislatures with personal vote systems should be more likely to seek assignment to committees with influence over policies affecting their constituents' economic interests than representatives elected in non-personal vote systems. In line with these arguments, previous research has found that representatives elected under electoral rules incentivizing personal vote seeking are more constituency oriented than those elected under rules that deemphasise individual candidates (André, Freire, and Papp, 2014;Stratmann and Baur, 2002;Heitshusen, Young, and Wood, 2005;André, Depauw, and Martin, 2016b). If representatives elected under electoral rules inhibiting identification of individual representatives are less constituency-oriented, they will be less likely to seek assignment to committees helping them to represent their constituents' preferences.…”
Section: Factors Potentially Influencing Committee Selectionmentioning
confidence: 90%